ANALISIS PERBANDINGAN PENDAPATAN PETANI PLASMA KELAPA SAWIT SEBELUM DAN SETELAH ADANYA WABAH COVID-19 DI DESA PAJAR INDAH KECAMATAN GUNUNG MEGANG KABUPATEN MUARA ENIM - Khotimah, Mirna; Ningrum, Puri Pratami Ardina (Universitas Muhammadiyah Palembang, 2021)
The purpose of this study was to determine the income of oil palm plasma farmers before and after the covid-19 outbreak in Pajar Indah Village, Gunung Megang District, Muara Enim Regency and to determine the comparison of the income of oil palm plasma farmers before and after the covid-19 outbreak in Pajar Indah Village. Gunung Megang District, Muara Enim Regency. This research was conducted in Pajar Indah Village, Gunung Megang District, Muara Enim Regency from August to October 2020. The research method used was a survey. The sampling method used was simple random sampling. The data collection methods used in this study were interviews, observation and documentation. The data processing method in this research is using quantitative descriptive method. The results showed that the income of oil palm plasma farmers before the Covid-19 outbreak was Rp. 19.782.517,83, expanding cultivated per three months or Rp. 66.640.131,67 per hectare per three months. Meanwhile, the income of oil palm plasma farmers after the Covid-19 outbreak was IDR 17.551.766,67, expanding their cultivation every three months or IDR 5.887.526,53. From the t-test shows that the t-count is 0.00 with df that is 29, then the t-table value is 1.699. Due to the t-count value of 0,00 ? t-table 1,699, H0 is accepted and Ha is rejected, meaning that there is a significant difference in income between oil palm plasma farmers before the covid-19 outbreak and after the covid-19 outbreak.